Cognitive functions and modifiable risk factors for chronic non-communicable diseases in ageing in a Russian population sample. - Titarenko, A V; Shishkin, S V; Shcherbakova, L V; Verevkin, E G; Shapkina, M Y; Hubacek, J A; Bobak, M; Malyutina, S K (Advances in gerontology, 2022)
We aimed to investigate the relationship between the indicators of cognitive functions (CF) and modifiable risk factors for chronic non-communicable diseases (NCD) in a cross-sectional analysis in the urban Russian population sample aged 55-84 years. The study investigated a random sample of 3 153 people (men and women 55-84 years old) from a general population cohort of Novosibirsk residents; a sample was examined within the international project HAPIEE. The study protocol included standardized neuropsychological tests (quantitative assessment of memory, semantic verbal fluency, attention and processing speed) and standardized assessment of risk factors, history and treatment of cardiovascular disease and NCD. In cross-sectional analysis we observed a positive relationship of CF indices with level of education and an inverse relationship with metabolic risk factors and smoking in both sexes. The level of total cholesterol and moderate alcohol consumption had positive relationship with CF indices in women. These associations were independent from age and other factors.
Keywords: Aging; Cognition; mužské pohlaví; Male; senioři; senioři nad 80 let; Humans; Female; Noncommunicable Diseases; lidé; risk factors for chronic non-communicable diseases; Cross-Sectional Studies; ženské pohlaví; kognice; rizikové faktory; Aged, 80 and over; neinfekční nemoci; stárnutí; Risk Factors; population; průřezové studie; cognitive functions; Aged; aging